2018
DOI: 10.1007/s10494-018-9909-3
|View full text |Cite
|
Sign up to set email alerts
|

A Thickened-Hole Model for Large Eddy Simulations over Multiperforated Liners

Abstract: In aero-engines, mutiperforation cooling systems are often used to shield the combustor wall and ensure durability of the engine. Fresh air coming from the casing goes through thousands of angled perforations and forms a film which protects the liner. When performing Large Eddy Simulations (LES) of a real engine, the number of sub-millimetric holes is far too large to allow a complete and accurate description of each aperture. Homogeneous models allow to simulate multiperforated plates with a mesh size bigger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…For combustion, the thickened-flame model (Colin et al, 2000) is used to account for combustion-turbulence interaction along with a reduced chemistry with 6 species and 2 reactions (Franzelli et al, 2010) where a purely gaseous premixed mixture is injected. In addition, the thickened-hole model (Bizzari et al, 2018) is introduced to represent the micro-perforations in the flame-tube. Non-reflective Navier-Stokes characteristic boundary conditions are used at inlet (Poinsot and Lele, 1992;Odier et al, 2019) and outlet (Granet et al, 2010;Koupper et al, 2015) without any kind of synthetic turbulence.…”
Section: Numerical Setupmentioning
confidence: 99%
“…For combustion, the thickened-flame model (Colin et al, 2000) is used to account for combustion-turbulence interaction along with a reduced chemistry with 6 species and 2 reactions (Franzelli et al, 2010) where a purely gaseous premixed mixture is injected. In addition, the thickened-hole model (Bizzari et al, 2018) is introduced to represent the micro-perforations in the flame-tube. Non-reflective Navier-Stokes characteristic boundary conditions are used at inlet (Poinsot and Lele, 1992;Odier et al, 2019) and outlet (Granet et al, 2010;Koupper et al, 2015) without any kind of synthetic turbulence.…”
Section: Numerical Setupmentioning
confidence: 99%
“…The flow then enters the flame-tube through the top and bottom dilution and primary holes; the swirlers farther back; and through the modelled multi-perforations of the flame-tube (Bizzari et al, 2018). In this case, each modelled perforation is set to either a constant suction or an injection of mass-flow rate at a determined temperature by the flame-tube side.…”
Section: Comparison Of the Combustion Chamber Predictionsmentioning
confidence: 99%
“…In this case, this shift is caused by the change in angle of the jets issued from the primary and dilution holes depicted in Figure 16. Values of T t,RMS are characterised in both cases by higher levels near the hub and the casing which are generated by the mixing of the cold jets from the multi-perforated flame-tube (with the thickened-hole model by Bizzari et al (2018)) and the hot flow from combustion. These jets can be seen in the shroud of Figure 18b and 18d.…”
Section: Comparison Of the Combustion Chamber Predictionsmentioning
confidence: 99%
“…It consists of two parallel channels communicating through 144 converging holes disposed in 12 staggered rows as shown in Fig. 4 and described in [38,11].…”
Section: Flow Configurationmentioning
confidence: 99%
“…The mesh considered is composed of about one million of elements. The ratio between the hole diameter and the mesh size, as introduced in Bizzari et al [11], is equal to one; this corresponds to the typical mesh size found in numerical simulation of real combustors.…”
Section: Validation Of the Reference Temperature Estimatormentioning
confidence: 99%